2015
DOI: 10.1016/j.jmmm.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

On the shape of the magnetic Barkhausen noise profile for better revelation of the effect of microstructures on the magnetisation process in ferritic steels

Abstract: a b s t r a c tThe shape of the Magnetic Barkhausen Noise (MBN) profiles has been compared for two different methods of MBN measurements in order to reveal the true extent of the influence of different carboncontent related microstructures on the magnetisation process. The MBN profiles were measured using high frequency and low frequency MBN measurement systems on samples from low carbon 18CrNiMo5 steel and high carbon 42CrMo4 steel heat treated by isothermal annealing, spheroidising annealing and quenching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…They have extended their experiment by using high and low frequency for MBN measurement systems on samples of low carbon and high carbon steel. The high-frequency (= 125 Hz) MBN profile showed single peak for all the samples due to insufficient applied field strength (188 Oe) and shallow magnetic skin depth, whereas low-frequency (= 0.4 Hz) MBN profile showed two peaks due to greater magnetization inside the bulk material [24]. Magnetic Barkhausen noise signal at high frequency range should be obtained to derive necessary information of the surface inhomogeneities, caused by high cutting force and temperature due to local shear deformation at the tool-workpiece contact during machining.…”
Section: Introductionmentioning
confidence: 90%
“…They have extended their experiment by using high and low frequency for MBN measurement systems on samples of low carbon and high carbon steel. The high-frequency (= 125 Hz) MBN profile showed single peak for all the samples due to insufficient applied field strength (188 Oe) and shallow magnetic skin depth, whereas low-frequency (= 0.4 Hz) MBN profile showed two peaks due to greater magnetization inside the bulk material [24]. Magnetic Barkhausen noise signal at high frequency range should be obtained to derive necessary information of the surface inhomogeneities, caused by high cutting force and temperature due to local shear deformation at the tool-workpiece contact during machining.…”
Section: Introductionmentioning
confidence: 90%
“…The first peak in low magnetic field strength is related to the nucleation and annihilation of domain walls in grain boundaries of ferrite and the second peak at higher amplitude position indicates the displacement of domain walls due to the second phase particles which are harder pearlites in samples. 2 It is obvious that the shapes of profiles for different samples change slightly with the change of the relative position of two peaks. From (a) to (d) in Fig.…”
Section: A Carbon Contentmentioning
confidence: 98%
“…1 Vashista et al used two Gaussian curves to fit the two peaks of 18NiCrMo5 steel with different treatments and extracted parameters of two peaks include peak height, peak position and the full width of half maximum. 2 In this paper, we proposed a novel approach to study the relationship between MBN signal and carbon content of samples by introducing new quantitative analysis method and multi-objective sensor optimization. Parameter gap between two peaks (∆G) extracted from a fitting curve fitted by two Gaussian curves shows a linear relationship with the carbon content.…”
Section: Introductionmentioning
confidence: 99%
“…In quenched and tempered (QT) sample, it has been shown that the domain walls could also move easily in low carbon tempered martensitic laths structure resulting in high level of Magnetic Barkhausen Noise (MBN) signals [21]. The martensitic lath boundaries could act similar to the grain boundaries.…”
Section: Effect Of Microstructures On the Datf Profilementioning
confidence: 99%